2011
DOI: 10.21161/mjm.24410
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment method for the isolation of bioactive actinomycetes from mangrove sediments of Andaman Islands, India

Abstract: Various pre-treatment methods and three different media were employed for the isolation of bioactive actinomycetes from mangrove sediments of Andaman and Nicobar Islands, India. Sediments from four different sites of mangrove forest were collected and pre-treated by dry heat method, and the media were supplemented with cycloheximide 80 μg/mL and nalidixic acid 75 μg/mL. The mean actinomycetes population density in sediment samples were recorded as 22 CFU-10-6 /gm in KUA medium followed by 12 CFU-10-6 /gm in AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 16 publications
(18 reference statements)
4
60
0
Order By: Relevance
“…Baskaran et al reports that starch casein agar, Kuster's agar was found to be good for isolation of marine actinobacteria population. However, in the present study the maximum number of colonies was isolated on AIA followed by kuster's agar [40] . Hence, the soil physicochemical properties may play a major role in the selection of isolation media.…”
Section: Discussionmentioning
confidence: 55%
“…Baskaran et al reports that starch casein agar, Kuster's agar was found to be good for isolation of marine actinobacteria population. However, in the present study the maximum number of colonies was isolated on AIA followed by kuster's agar [40] . Hence, the soil physicochemical properties may play a major role in the selection of isolation media.…”
Section: Discussionmentioning
confidence: 55%
“…Many potential bacteria were isolated from mangrove ecosystem such as nitrogen-fixers, phosphate solubilizers, photosynthetic anoxygenic sulfur bacteria, methanogenic and methane oxidizing bacteria, which are involved in efficient nutrient recycling [79]. Also bacteria and fungi that either produce antibiotics [80,81] or resistant to antibiotics were isolated from mangrove ecosystem [82,83].…”
Section: Mangrovementioning
confidence: 99%
“…Slow growing, melanotrophic actinobacteria Actinobacteria Isolating Agar (AIA) Minimal medium Fast and slow growing actinobacteria (Baskaran et al, 2011) Defined Propionate Medium (DPM) and Buffered Ammonium Propionate (BAP) Specific for Frankia species (Gtari et al, 2004) International Streptomyces Project (ISP) Media (1 to 9)…”
Section: Medium Properties Referencesmentioning
confidence: 99%
“…Actinobacteria Isolating Agar (AIA) has also been suggested as a selective medium for actinobacteria in sediments (Baskaran et al, 2011). The ISP (International Streptomyces Project) family media have been used for studying physiological characteristics of already isolated actinobacteria.…”
Section: Actinobacteria Isolationmentioning
confidence: 99%
See 1 more Smart Citation